2019
DOI: 10.1002/ijc.32159
|View full text |Cite
|
Sign up to set email alerts
|

The genomic imprint of cancer therapies helps timing the formation of metastases

Abstract: A retrospective determination of the time of metastasis formation is essential for a better understanding of the evolution of oligometastatic cancer. This study was based on the hypothesis that genomic alterations induced by cancer therapies could be used to determine the temporal order of the treatment and the formation of metastases. We analysed the whole genome sequence of a primary tumour sample and three metastatic sites derived from autopsy samples from a young never‐smoker lung adenocarcinoma patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…A simple method for ascertaining whether a given metastasis arose before or after treatment with cisplatin or an alkylator is to find clonal SNVs attributed to the respective signature in a metastatic tumor sample 27 . When looking at the dominant clone in the first relapse sample for patients with recurrent disease (OSCE1-Clone D, OSCE4-Clone E/I, OSCE5-Clone C, OSCE6-Clone C/F/G, OSCE9-Clone C/G, OSCE10-Clone C/F), there was a cisplatin signature present in each of these respective clones/clades, indicating that the metastases arose after therapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A simple method for ascertaining whether a given metastasis arose before or after treatment with cisplatin or an alkylator is to find clonal SNVs attributed to the respective signature in a metastatic tumor sample 27 . When looking at the dominant clone in the first relapse sample for patients with recurrent disease (OSCE1-Clone D, OSCE4-Clone E/I, OSCE5-Clone C, OSCE6-Clone C/F/G, OSCE9-Clone C/G, OSCE10-Clone C/F), there was a cisplatin signature present in each of these respective clones/clades, indicating that the metastases arose after therapy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Annak illusztrálására, hogy klinikailag milyen jelentősége lehet a kemoterápiás szerek mutagén hatásának részletes leírása, az MTA Enzimológiai Intézetének Genom Stabilitás Kutatócsoportjával végzett kutatásunk [166] során egy fiatal tüdődaganatos férfi többszörös metasztázisainak törzsfáját határoztuk meg a ciszplatin genomi lenyomatának ismeretében. A DT40 sejtvonal ciszplatin mutációs spektrumának meghatározása után nem sokkal a ciszplatin humán sejtvonalakra, illetve daganatsejtekre gyakorolt hatását is feltérképezték [167].…”
Section: Metasztázisok Törzsfájának Meghatározása a Genomi Mutációk A...unclassified
“…The mutagenicity of cisplatin has been investigated and reported using prokaryotic and eukaryotic reporter gene assays (reviewed by 31,32) and by whole genome sequencing of animals or cell lines (33)(34)(35)(36). The mutagenic footprint of platinum treatment was subsequently also found in the genomes of primary tumours (35,37,38) and metastases (39,40). In comparative studies, cisplatin and carboplatin were found to be similarly mutagenic in the Salmonella histidine reversion assay when a higher concentration of carboplatin was used (41), and cisplatin was found to be more mutagenic than oxaliplatin in the HPRT gene of mammalian cells at equimolar concentrations (42).…”
Section: Introductionmentioning
confidence: 99%